(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
Monetary policy is one of the most powerful instruments of economic policy owned by the state. This is a set of measures aimed at changing the money supply, loan amount, interest rate and regulation of the banking system as a whole. That is why the article discusses the main issues of monetary policy and its development trends. In other words, what methods and tools are currently used by the National Bank of the Republic of Kazakhstan, their main advantages and disadvantages, macroeconomic results of monetary policy. In this regard, the purpose of this article is to study the financial and credit methods of state regulation of the economy of the Republic of Kazakhstan and the concept of monetary policy. The study used economic methods used in the study of economic conditions. The article analyzes the situation and indicators of monetary policy for the last two years of 2017 and 2018, as well as changes and trends in monetary policy in 2019. In 2018, the National Bank focused on the further development of the money and foreign exchange market, as well as the government securities market, and demonstrated the importance of a number of initiatives aimed at improving the effectiveness of monetary policy. The results of the study allow students to apply them during their studies.